2003
DOI: 10.1051/kmae:2003006
|View full text |Cite
|
Sign up to set email alerts
|

Management of the White-Clawed Crayfish (Austropotamobius Pallipes) in Western France: Abiotic and Biotic Factors Study

Abstract: In France, the distribution of the white-clawed crayfish, Austropotamobius pallipes (Lereboullet, 1858), is restricted, fragmented and mainly located in headwaters. To preserve this indigenous species, it is necessary to characterize its ecological requirements (water and habitat quality). With this aim in view, a two-year study is being conducted in the Deux-Sèvres department (Western France) since November 2002. Nine brooks from four different catchments are monitored regularly; eight of the nine brooks harb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 14 publications
4
25
0
Order By: Relevance
“…Gherardi et al 1996;Grandjean et al 1998Grandjean et al , 2000Grandjean et al , 2003Largiarder et al 2000;Demers et al 2003;Trouilhe et al 2003;Fratini et al 2005). This provides enough information to preserve this species in situ.…”
Section: Introductionmentioning
confidence: 99%
“…Gherardi et al 1996;Grandjean et al 1998Grandjean et al , 2000Grandjean et al , 2003Largiarder et al 2000;Demers et al 2003;Trouilhe et al 2003;Fratini et al 2005). This provides enough information to preserve this species in situ.…”
Section: Introductionmentioning
confidence: 99%
“…Three notable exceptions relative to European rivers have been documented, however. Broquet et al (2002), Trouilhé et al (2003) and Trouilhé et al (2007) have reported some French populations of A. pallipes to inhabit waters with substantially higher nitrate concentrations than other authors. Our field survey found a range of nitrate concentrations in waters inhabited by A. pallipes very similar to those of European rivers.…”
mentioning
confidence: 79%
“…Others, for example Broquet et al (2002), noted crayfish in higher concentrations than the range of European means, but with values that fell within the range of global means. It has been suggested that a lower limit of 5 mg·L −1 calcium concentration restricts the presence of A. pallipes (Greenaway, 1974), as supported by observations of Jay and Holdich (1981) and Smith et al (1996) (Reyjol and Roqueplo, 2002) and one as low as 1 mg·L −1 (Trouilhé et al, 2003). Crayfish can, therefore, evidently survive below the proposed 5 mg·L −1 threshold.…”
Section: > Calcium [Ca 2+ ]mentioning
confidence: 92%
“…Indeed, several studies have shown that habitat heterogeneity, water quality and lack of pollutants enhance or ensure the survival of some indigenous species (e.g. Trouilhé et al, 2003). Often, the decline or the extinction of indigenous crayfish has been observed in areas with extensive land use, crayfish being highly sensitive to a great variety of fertilizers, insecticides and pesticides (Eversole et al, 1995).…”
Section: Indirect Use As Surrogate Speciesmentioning
confidence: 99%